The Structure of Discussions in an Online Communication Course: What Do Students Find Most Effective? - Jacobi, Laura (Journal of University Teaching and Learning Practice, 2017)
The purpose of this study was to explore the perspectives of students regarding what was effective about the way in which the asynchronous discussions were structured in an upper level online organizational communication course. Surveys from 27 student participants were used, with questions focused upon the structure of discussions in the online course as compared to other online courses and to traditional classrooms. Results indicate structured and relevant discussion prompts, small group placement, visible postings, and required weekly postings as significant factors to student success. The majority of students also found online discussions more effective than live discussions in traditional classrooms. Many of the findings offer support for Garrison, Anderson, and Archer’s (2000) Community of Inquiry (COI) Model and previous research on effective strategies in structuring online discussions.